2022
DOI: 10.1371/journal.pntd.0010506
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the duration of antibody positivity and likely time of Leptospira infection using data from a cross-sectional serological study in Fiji

Abstract: Background Leptospirosis is a zoonotic disease prevalent throughout the world, but with particularly high burden in Oceania (including the Pacific Island Countries and Territories). Leptospirosis is endemic in Fiji, with outbreaks often occurring following heavy rainfall and flooding. As a result of non-specific clinical manifestation and diagnostic challenges, cases are often misdiagnosed or under-ascertained. Furthermore, little is known about the duration of persistence of antibodies to leptospirosis, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…While it is conventionally characterized that younger adult age groups are at higher risk (12,13), our findings are consistent with previous studies in the city of Salvador that have also identified a linear trend with age (4,15). This may also be partially attributable to the persistence of antibodies, which can remain detectable for several years following exposure and reflects a limitation of this study (53). The persistence of antibodies over several years presents additional challenges as behaviours were self-reported during the previous six months as a measure of exposure risk (53).…”
Section: Discussionmentioning
confidence: 94%
“…While it is conventionally characterized that younger adult age groups are at higher risk (12,13), our findings are consistent with previous studies in the city of Salvador that have also identified a linear trend with age (4,15). This may also be partially attributable to the persistence of antibodies, which can remain detectable for several years following exposure and reflects a limitation of this study (53). The persistence of antibodies over several years presents additional challenges as behaviours were self-reported during the previous six months as a measure of exposure risk (53).…”
Section: Discussionmentioning
confidence: 94%
“…This is further compounded, as, to conserve testing capability, once a leptospirosis outbreak has been declared, it is recommended that diagnosis is done based on case definitions and clinical judgement [ 34 ]. Therefore, the cases and the outbreaks reported by the ELISA-positive data are likely to be a small fraction of the true cases occurring in Fiji [ 58 ]. Furthermore, changes in case detection, case reporting and diagnostic capabilities have occurred over time.…”
Section: Discussionmentioning
confidence: 99%
“…This association has also been seen in previous Caribbean serosurveys [ 30 , 31 ]. While acute cases tend to occur in young and middle-aged adults most often, anti- Leptospira antibodies can persist for several years, sometimes up to a decade or more [ 33 , 46 ]. Notably, two seropositive participants were children aged five and thirteen years.…”
Section: Discussionmentioning
confidence: 99%